Effects of high-intensity isokinetic exercise on salivary cortisol in athletes with different training schedules: Relationships to serum cortisol and lactate - Paccotti, P.; Minetto, M.; Terzolo, M.; Ventura, M.; Ganzit, G. P.; Borrione, P.; Termine, A.; Angeli, A. (International Journal of Sports Medicine, 2005)
Physical exercise is associated with increases of serum and salivary levels of cortisol. The concomitant increase in serum lactate has been implicated as one of the mechanisms responsible for adrenocortical activation. We evaluated the responses of serum lactate and serum and salivary cortisol to an acute bout of high-intensity isokinetic exercise in eleven non-competitive and twenty competitive athletes (NCA and CA, respectively). The latter group was composed of endurance- and power-trained athletes (EA and PA, respectively). Aims of the study were to determine interindividual differences in the lactate and cortisol responses as a function of type and intensity of training and to search for relationships both between lactate and cortisol production and between serum and salivary cortisol levels.